Nature-engagement and wellbeing in Brazil: Understanding the dose-effect relationship for designing urban green spaces - Bressane, Adriano [UNESP]; Loureiro, Anna Isabel Silva [UNESP]; César de Castro Medeiros, Líliam [UNESP] (Elsevier, 2024)
Statement of problem: In the face of increasing urbanization, the pursuit of healthy and sustainable cities promoting a high quality of life intertwined with nature is paramount. Purpose: This research endeavors to assess the impact of variations in nature interaction styles on health, with the objective of generating evidence to inform the design of urban green spaces. Method: Ethically approved by the Human Research Ethics Committee (CAAE 58149622.3.0000.0077), a survey involving 2136 respondents was conducted. Participants reported their nature engagement frequency, duration, and intensity, alongside mental health assessments using the Depression, Anxiety, and Stress Scale (DASS-21). Welch's ANOVA and Cohen's d were employed to derive meaningful effect size. Conclusions: This research provided empirical insights into the relationship between nature interaction and public health, thus offering evidence to inform urban green space design. Practical implications: The findings are expected to empower urban planners and policymakers with evidence-based strategies for creating urban green spaces conducive to physical activities, leisure events, and nature-based recreation, promoting public health through appropriately timed and frequented activities. Future directions: Further research avenues may include longitudinal studies to assess the long-term impact of nature interaction on mental health and the implementation of evidence-based design strategies in urban green space development.
Keywords: Green spaces; Urban infrastructure; Urban planning, public health